PENERAPAN SANKSI TERHADAP PENYALAHGUNAAN OBAT KERAS PIL DOUBLE L DITINJAU DARI UU NO. 36 TAHUN 2009 TENTANG KESEHATAN: Studi Putusan Nomor :38/Pid.Sus/2022/PN Mlg - Solikin, Ma’rifatus; Sutrisno, Sutrisno (Gapenas Publisher, 2023)
Hard drugs are currently easily circulating in the community. Various types of hard drugs are obtained by the community due to irresponsible parties. This causes hard drugs, especially double L pills, to be very easy to consume and abuse. This study aims to find out what laws apply in Indonesia regarding the abuse of double L pills and to find out what efforts are made by drug abusers of doubel L pills. The type of research used in this research is empirical juridical with a conceptual approach, legislative approach and case approach. Primary data and secondary data are obtained by observation, interview, and literature study. The method of data analysis in this research is deductive data analysis method, which uses a way of explaining about related data and has a general nature to determine conclusions that have a special nature. The result of this research is that sanctions that can be applied to double L pill abusers if the abuser of double L pills is only limited to consumption without other purposes, the perpetrator cannot be convicted. This is due to the absence of regulations governing the criminalization of people who consume hard drugs double L pills. The abused double L pills will be confiscated by the prosecutor's office and then destroyed. Law enforcers have preventive efforts in the form of legal counseling to overcome the abuse of double L pills